Advances in electrochemical biosensors for the detection of tumor-derived exosomes - Chen, Jun; Zhao, Zhou; Zhu, Honglin; Li, Xiaobing (Frontiers in Chemistry, 2025)
Exosomes, released from diverse cells as nanoscale lipid bilayer vesicles, mediate intercellular communication and participate in various physiological and pathological processes. Thereinto, tumor-derived exosomes (T-EXOs) with molecular cargoes of parent tumor cells act as attractive biomarkers for tumor liquid biopsy. The amount of T-EXOs and their levels of contained specific proteins and nucleic acids are closely associated with cancer burden and classification. Nevertheless, the nanoscale size and relatively low abundance of exosomes, as well as complex body liquid matrix pose daunting challenges for efficient isolation and sensitive detection of T-EXOs. Biosensing as fast, convenient and accurate method, has been widely employed for the detection of biomarkers over the past decades. Among them, electrochemical sensors can sensitively detect biomarkers by measuring of the change of electrical signal caused by oxidation or reduction at the working electrode surface. This review aims to summarize the recent advance in electrochemical biosensors for quantification, and protein and RNA analysis of exosomes. Further, challenges and future perspectives for exosome-based liquid biopsy have been discussed.